Preparedness for, and Resilience to, Terrorism: bibliography 60+ Full-Text Academic Theses (Ph.D. and M.A.) written in English between 2000 and 2020 - McDonald, Broderick (Perspectives on terrorism, 2021)
This bibliography contains Ph.D. Dissertations (Ph.D.) and Master Theses (M.A.) on issues relating to preparedness for, and resilience to, terrorism. Titles were retrieved manually by searching the Open Access Theses and Dissertations Database (OATD), using various combinations of search terms, including - but not limited to - ‘Terrorism’, ‘Violent Extremism’, ‘Resilience, and Preparedness. More than 850 entries were evaluated, of which 63 were ultimately selected for this list. All theses are open source. However, readers should observe possible copyright restrictions. The title entries below are hyperlinked, or ‘clickable’, allowing access to full texts.